Ciberbullying en los estudiantes de la UE. Cristiana Nazareno - Muyulema Villagómez, Vinicio Alexander (2021)
The purpose of this research work was to study cyberbullying in the students of the Unified General High School “Unidad Educativa Cristiana Nazareno." The research variable was analyzed; cyberbullying, a problem linked to harassment through the internet and social networks which have affected whole society, especially adolescents within their educational context, with the respective theoretical and conceptual foundation, with its field analysis. The purpose of this research work was to study cyberbullying in the students of the Unified General High School “Unidad Educativa Cristiana Nazareno." The research variable was analyzed; cyberbullying, a problem linked to harassment through the internet and social networks that have affected whole society, especially adolescents within their educational context, with the respective theoretical and conceptual foundation, with its field analysis. The research had a quantitative approach; the design was non-experimental; the research type was descriptive and correlational, for the transversal time and purpose, it was basic. While for the place it was of the field, the population was made up of a total sample of 34 men and 42 women; students of the General Unified high school. “Cyberbullying Questionnaire” was used questionnaire, it demonstrated that within the institution cyberbullying is practiced with modalities such as electronic insults, cyber persecution, disclosure, enticement, harassment, and impersonation. These results affirm that 2 out of 10 students of the "Unidad Educativa Cristiana Nazareno" suffer from virtual school bullying or cyberbullying occasionally and/or permanently.